Development of chitosan/fish scales collagen/glycerin/ nano-ZnO 3D porous scaffolds for skin tissue engineering and regeneration applications - Saleem Ullah (Tanjong Malim, 2018)
Development of chitosan/fish scales collagen/glycerin/ nano-ZnO 3D porous scaffolds for skin tissue engineering and regeneration applications by Saleem Ullah